Bidirectional variation in glutamate efflux in the medial prefrontal cortex induced by selective positive and negative allosteric mGluR5 modulators. Issue 2 (12th February 2018) - Isherwood, Sarah N.; Robbins, Trevor W.; Dalley, Jeffrey W.; Pekcec, Anton
Abstract: Dysregulation of prefrontal cortical glutamatergic signalling via NMDA receptor hypofunction has been implicated in cognitive dysfunction and impaired inhibitory control in such neuropsychiatric disorders as schizophrenia, attention‐deficit hyperactivity disorder and drug addiction. Although NMDA receptors functionally interact with metabotropic glutamate receptor 5 (mGluR5), the consequence of this interaction for glutamate release in the prefrontal cortex (PFC) remains unknown. We therefore investigated the effects of positive and negative allosteric mGluR5 modulation on changes in extracellular glutamate efflux in the medial PFC (mPFC) induced by systemic administration of the non‐competitive NMDA receptor antagonist dizocilpine (or MK801) in rats. Extracellular glutamate efflux was measured following systemic administration of the positive allosteric mGluR5 modulator [S‐(4‐Fluoro‐phenyl)‐3‐[3‐(4‐fluoro‐phenyl)‐[1, 2, 4]‐oxadiazol‐5‐yl]‐piperidin‐1‐yl‐methanone] (ADX47273; 100 mg/kg, p.o.) and negative allosteric mGluR5 modulator [2‐chloro‐4‐[1‐(4‐fluorophenyl)‐2, 5‐dimethyl‐1H‐imidazol‐4‐yl]ethynylpyridine] (RO4917523; 0.3 mg/kg, p.o.), using a wireless glutamate biosensor in awake, freely moving rats. The effect of MK801 (0.03–0.06 mg/kg, s.c.) on mPFC glutamate efflux was also investigated in addition to the effects of MK801 (0.03 mg/kg, s.c.) following ADX47273 (100 mg/kg, p.o.) pre‐treatment. ADX47273 produced a sustained increase in glutamate efflux and increased the effect of NMDA receptor antagonism on glutamate efflux in the mPFC. In contrast, negative allosteric mGluR5 modulation with RO4917523 decreased glutamate efflux in the mPFC. These findings indicate that positive and negative allosteric mGluR5 modulators produce long lasting and opposing actions on extracellular glutamate efflux in the mPFC. Positive and negative allosteric modulators of mGluR5 may therefore be viable therapeutic agents to correct abnormalities in glutamatergic signalling present in a range of neuropsychiatric disorders. Abstract : NMDA‐receptor‐dependent abnormal prefrontal glutamatergic signalling is linked to neuropsychiatric disorders. Although NMDA receptors interact with mGluR5, the consequence on glutamate efflux remains unknown. We demonstrate that mGluR5‐positive allosteric modulation (PAM) increased prefrontal glutamate efflux and potentiated the effect of NMDA receptor antagonism, whereas negative allosteric modulation (NAM) decreased this measure. These agents may correct glutamatergic abnormalities clinically.